Interventions to improve the uptake of screening across a range of conditions in Ethnic Minority Groups: a systematic review. Issue 8 (19th June 2018) - Kelly, Claire; Pericleous, Marinos; Hendy, Jane; de Lusignan, Simon; Ahmed, Ayesha; Vandrevala, Tushna; Ala, Aftab
Summary: Background: Screening programmes are well established in cancer, and are now being implemented in other conditions. An effective screening programme leads to early disease detection and improved outcomes but its impact is dependent on the quality of the test and the proportion of the target population participating. A further consideration is that uptake of screening by minority groups is low. Purpose: To determine which interventions have successfully increased screening uptake amongst minorities. Data sources: Medline, Cochrane database and the grey literature were searched from 1990 to 1st March 2016. Study selection: Fifty‐five English language studies that assessed uptake of screening in any minority population in the country of study aged over 18 years and that included a comparison arm. Data extraction: Independent data extraction was undertaken by two researchers (CK and MP), using a predesigned data extraction form (DEF) which assisted retrieval of the core contents of each study and the organisation of material. Data synthesis: Evidence was organised by screening test and type of intervention. Two authors (CK and MP) extracted data into evidence tables to enable comparison of study characteristics and findings. The heterogeneity of methods precluded a meta‐analysis thus results are descriptive. Evidence was also assessed, using the Cochrane Collaboration risk of bias tables. Results: This systematic review appraises data from international studies on a variety of minority groups, interventions and screening programmes providing a narrative review of their success and limitations.